Automated Office Blood Pressure and the Impact of Attendance and Rest on Diagnostic Accuracy. (3rd March 2022) - Green, Beverly B; Anderson, Melissa L; Cook, Andrea J; Ehrlich, Kelly; Hall, Yoshio N; Margolis, Karen L; Thompson, Matthew J
Abstract: Background: Automated office blood pressure (AOBP) using 3–5 measurements taken with an oscillometric device with or without an attendant in the room may decrease "white coat" effect. We evaluated the impact of the presence or absence of the attendant and rest on BP and diagnosis of hypertension. Methods: We randomly assigned 133 adults aged 18–85 with high BP at baseline (≥140/90 mm Hg), no hypertensive diagnosis and no antihypertensive medications to either attended AOBP first, unattended second, or unattended AOBP first, attended second. Outcomes included within-person BP difference for attended vs. unattended measurements; 5 vs. 15 minutes of rest; and the diagnostic performance of AOBP compared with daytime automated blood pressure measurement (ABPM). Results: We found no significant differences between attended and unattended AOBP (mean difference attended − unattended [95% confidence interval, CI], systolic 0.14 mm Hg [−0.78, 1.06]; diastolic 0.16 mm Hg [−0.45, 0.78]) or by rest time (mean difference 15 − 5 minutes [95% CI], systolic −0.45 mm Hg [−1.36, 0.47]; diastolic 0.61 mm Hg [−1.23, 0.003]). AOBP was lower than mean daytime ABPM, regardless of attendance or rest (after 5 minutes rest systolic −3.6 and diastolic −2.55 mm Hg, P = 0.001 for both comparisons). Using daytime ABPM of ≥135/85 mm Hg as the diagnostic threshold, AOBP sensitivity and specificity after 5 minutes of rest were 71.0% and 54.1%, respectively. Conclusions: The presence or absence of a clinic attendant during AOBP measurement and the amount of rest time before AOBP measurements had no effects on BP. AOBP measurements have low sensitivity and specificity for making a new diagnosis of hypertension. Graphical Abstract: